Overcoming negative stigma towards leprosy patients - Prakoeswa, Flora Ramona Sigit; Maharani, Faradiba; Sari, Winda Atika; Risanti, Erika Diana (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2025)
Background: Leprosy remains a public health problem, with various factors contributingo the transmission and progression of the disease. Stigma and discrimination towards leprosy patients have hindered the treatment and eradication of the disease.  Purpose: To identify the related factors and strategies to overcome stigmas towards leprosy patients. Review: Leprosy is a chronic infectious disease that affects skin and nerve, and causes visible permanent impairment if the patients do not get adequate treatment. Therefore, visible clinicalnifestations and cultural beliefs have createdigma towards leprosy patients, which negatively impacts their quality of life and their awareness of seeking health care. These factors may lead to patients avoiding diagnosis and treatment, which in turn increases number of G2D cases and transmission rate. Cultural and religious beliefs, low education level, and minimal information about leprosy have been known to contribute to the stigma. Several strategies can be considered to use to overcome stigma and discrimination towards leprosy patients. Conclusions: nderstanding factors related to leprosy stigma and its effects on the progression of the disease will help determine the strategies to overcome stigma and discrimination.